SAT0214 Reliability and Validity of the Italian Version of the Ucla-Scleroderma Clinical Trial Consortium-Gastrointestinal Tract Instrument in Patients with Systemic Sclerosis. (23rd January 2014) - Gualtierotti, R.; Ingegnoli, F.; Silvana, Z.; Ughi, N.; Ciavarella, T.; Becciolini, A.; Khanna, D.; Meroni, P. L.
Abstract : Background: Gastrointestinal tract (GIT) involvement is frequent (up to 90%) in patients with systemic sclerosis (SSc). The UCLA Scleroderma Clinical Trial Consortium GIT (UCLA-SCTC GIT) 2.0 is a validated instrument for measuring the presence, severity and impact of GI symptoms on the health-related quality of life (HRQOL). Objectives: To test the acceptability, feasibility, reliability and validity of the Italian translated version of UCLA-SCTC GIT 2.0. Methods: Translation was performed using the concept elaboration, two forward translations with reconciliation followed by two back translations with review. This was then reviewed by the developer (DK) and pilot tested in 5 patients, the transcript was reviewed and any inconsistencies reconciled. Acceptability and feasibility of the questionnaire were evaluated based on the comments of the patients. Internal consistency was evaluated by Cronbach's alpha. External consistency was measured by comparing with the SF-36 and EQ-5D by Spearman's rho rank correlation coefficient. We considered coefficients ≥0.30 as meaningful. Results: 20 consecutive SSc patients (mean age 57, 9) were recruited, 90% were female. Four patients had a diffuse cutaneous (dc)-SSc, 11 limited cutaneous (lc)-SSc and 5 had very early (ve)-Ssc based on EUSTAR classification [3]. 26, 3% had isolated anti-nuclear antibody positivity, 31, 6% had anti-centromere positivity and 42, 1% had anti-topoisomerase positivity. Mean disease duration since the first non-Raynaud symptom was 12, 6 years. The UCLA-SCTC GIT was well accepted by the patients and no additional comments were noted regarding the content of the instrument. Percentage of missing data in UCLA-SCTC GIT score was 3, 4% vs. 16% for SF-36 which has a similar number of total items. Internal consistency was good (alpha>0, 70) in all domains except for the Distention/Bloating domain (alpha=0, 53). Mean total UCLA-SCTC GIT score was 0, 37 (range 0-2, 83) and the worse scores were observed for Reflux (0, 40, range 0-3), Distention/bloating (0, 86, range 0-3) and for Constipation (0, 53, range 0-2, 5). GIT total score, Diarrhea and Fecal soilage domains significantly correlated with disease duration (p<0, 03; p<0, 05 and p<0, 05 respectively). UCLA-SCTC GIT Emotional Well-being was strongly correlated with the mental component summary of SF-36 (p<0, 03) and with the EQ-5D Self-care domain (p<0, 05). Reflux and Diarrhea domains correlated with the EQ-5D Usual Activities (p<0, 02 and p<0, 05) and Self-care domains (p<0, 01 for both), thus reflecting the impact on everyday and self-care activities. Conclusions: This is the first validation study of the Italian version of UCLA-SCTC GIT 2.0. Our data support its feasibility, reliability, and validity, in Italian SSc patients. Disclosure of Interest: None Declared